Biochemical Evaluation and Out Come of Hepatitis E in Pregnancy - Mohammed, Fazle Rabbi; Amin, Raihana; Ahasan, HAM Nazmul; Alam, Md Billal (Bangladesh Critical Care Journal, 2015)
Background: Viral hepatitis is common in Bangladesh. Hepatitis E virus is waterborne and usually self-limiting. But infection with Hepatitis E virus is a serious threat to pregnancy. In this study, we aimed to assess the clinical course and biochemical evaluation of hepatitis E during pregnancy. Materials & Methods: This descriptive observational study included 50 pregnant women having hepatitis E conducted from September, 2008 to September, 2011 in Dhaka Medical College Hospital. Every case was initially evaluated on the basis of history, clinical examination, liver function profile and serological test of hepatitis E. Result: Anti HEV IgM was detected in each case. Most of them (64%) were in third trimester and only 42% cases got boiled water. The mean value of serum bilirubin, alanine aminotransferase (ALT) and prothrombin time (PT) was 11.62 mg/dl ± 8.01 SD, 777.75 U/L ± 590.39 SD and 29.88 sec ± 12.54 SD respectively. Acute hepatic failure (AHF) was detected in 56% pregnant women. In this study, the death rate of Hepatitis E in pregnancy was 43%. Conclusion: During pregnancy, hepatitis E is associated with the development of acute hepatic failure (AHF) which has high mortality rate. Bangladesh Crit Care J September 2014; 2 (2): 65-67